Angle Discrete Interval Selection Technique (ADIST) On Optical Flow Vectors In Estimating Orientation Of Vision System - Zainal, Zairulazha (Institute of Electrical and Electronics Engineers, 2015)
In this paper,a method of extracting information in estimating orientation of vision system based on optical flow is presented.The method called angle discrete interval selection technique (ADIST) is proposed to estimate an angle by extracting optical flow information which consists less noise interference.The performance of ADIST is compared to the actual value and the errors are evaluated using root mean square error (RMSE) and mean absolute error (MAE).Comparison results between both evaluation method show that the smallest RMSE and MAE can be obtained using ADIST.Therefore,it is ascertained that our proposed method is useful to estimate orientation of vision system.